Intellectual property enforcement: remedies, procedures and processes in an international and EU copyright context - Cregan, Q (2018)
Copyright regulation has become increasingly transnational, if not global, in its approach. All aspects of copyright law have been impacted by efforts among nations to coordinate and harmonise their copyright regimes. As the United Kingdom coordinates its intellectual property regime with that of the European Union and globally, domestic judges must grapple with an increasing number of treaties, directives, and regulatory inputs which colour every step in the process of copyright enforcement. This research examines the expressions of how that coordination ought to, and does, impact domestic law. More specifically, this is a thesis about the Internationalisation and Europeanisation of remedies and procedures in UK copyright litigation. This thesis approaches this topic in three parts: Part One sets out the relevant framework of copyright regulation and protection in the United Kingdom from first principles (Chapter One). It explores the foundational instruments, the interaction between those instruments, and the overarching obligations stemming from those instruments which bear general application. This part identifes the inherent complexity and difficulties in properly applying these layered obligations (Chapter Two). Part Two takes the layered obligations and interactions from Part One and investigates how those interactions are in fact applied across the full spectrum of remedies, sanctions, and procedures. This is considered from the perspective of monetary remedies (such as damages) (Chapter Three), tangible and injunctive relief (Chapter Four), and criminal and declaratory outcomes (Chapter Five). Part Two concludes by looking at the degree of Europeanisation and Internationalisation of procedural obligations in copyright proceedings (Chapter Six). Part Three then reflects on the philosophy of such enforcement and its stated intended purposes (Chapter Seven) in light of the analysis undertaken in the previous chapters. The Part then argues that, based on the UK's experiences, the field of copyright remedies and procedure is, on an EU level, ripe for further harmonisation and reform to address systemic failures in properly applying transnational obligations. The Part makes a series of recommendations on improving outcomes, taking into account the purposes of copyright regulation by proposing the development of a harmonising EU regulation as the most viable course.